(untitled) (Research, Society and Development, 2022)
The material production of wealth through work allowed the ontological leap of the human race, allowing the transition from being biological to being social. It was based on teleologically oriented work that human beings were able to organize themselves in society. Therefore, work is understood as the founding activity of other human activities, being essential for the development of society. However, in the capitalist system, work ceased to be essential for the development of humankind, becoming essential for the development of capital, in which work has exchange value, not use value. That said, this study aims to reaffirm the Lukacsian view of work as a protoform of human activity, from which other forms of sociability originate. This is a qualitative bibliographical study, anchored in authors such as Karl Marx, Gyorgy Lukács and Sérgio Lessa, among other Marxist-based authors. As results and discussions, we pay attention to the fact that work is the prototype for other human activities, such as art, education, politics, etc. Although these activities, due to their specificities, maintain a relationship of autonomy with work, they also maintain a relationship of ontological dependence.